Early Childhood Education in Aotearoa New Zealand: History, Pedagogy, and Liberation - Ritchie, Jenny; Skerrett, Mere.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Taking as a starting point the work of Aotearoa New Zealand to provide an education system that includes curriculum, pedagogy, and language from indigenous Maori culture, this book investigates the ensuing practices, policies, and dilemmas that have arisen and provides a wealth of data on how truly culturally inclusive education might look.
Keywords: Science; Science; Science, general